A taxonomic revision of the Solanum echinatum group (Solanaceae) - Bean, A. R. (Phytotaxa, 2012)
The taxonomy of Solanum echinatum and its allies is revised. Seven species are enumerated, all endemic to tropical Australia, including four new species: S. fecundum sp. nov., S. lapidosum sp. nov., S. medicagineum sp. nov., and S. rhaphiotes sp. nov. Solanum longissimum is reduced to synonymy, and S. wilkinsii is reinstated. Illustrations are provided for all species. The distributions of all species are mapped, and an identification key is included.